The Effectiveness of Story Grammar Strategy in Teaching Reading Comprehension of Narrative Text - Musfirah; Mujahidah, Mujahidah; Sunubi, Abdul Haris; Zulfah; Ambo Dalle (IAIN KENDARI, 2025)
This study investigates the effectiveness of the Story Grammar Strategy in improving students’ reading comprehension of narrative texts. Utilizing a Classroom Action Research approach, the research was conducted in two cycles comprising planning, implementation, observation, and reflection stages. The participants consisted of 35 eleventh-grade students. The results showed a substantial improvement in reading comprehension scores, with the average increasing from 55.07 in the first cycle to 89.71 in the second cycle. Students demonstrated enhanced abilities in identifying narrative elements such as setting, characters, conflict, and resolution, along with increased engagement and motivation during learning activities. The findings suggest that the Story Grammar Strategy is an effective instructional method that fosters both cognitive and affective development in reading narrative texts within EFL classrooms.